CycloBranch: An open tool for fine isotope structures in conventional and product ion mass spectra - Novák, Jiří; Škríba, Anton; Zápal, Jakub; Kuzma, Marek; Havlíček, Vladimír (Journal of mass spectrometry, 2018)
Within the growing community of Fourier transform mass spectrometry users, the identification of fine isotope structure has become an indispensable method for molecular formula determination. In this work, the fine isotope envelopes for accessing the mutual ratio of 2 closely related pyoverdines in a mixture were used. Bacterial siderophores pyoverdines D and E cannot be easily separated via liquid chromatography-mass spectrometry because their structures differ in (de)amidation at the respective chromophore parts only. Their mutual ratio was determined in a mixture via nuclear magnetic resonance spectroscopy and semiquantitative mass spectrometry using our open-source software CycloBranch, which represents a genuine free tool supporting the determination of fine isotope structures in both conventional and product ion mass spectra. Native Bruker, Thermo, and Waters data formats are supported in addition to XML and plain text formats.
Keywords: NMR; quantitation; fine isotope structure; CycloBranch; pyoverdine; mass spectrum